Factors Affecting the Wisdom of Counselors: Perceptions of Indonesian Pre-service Counselors - Herdi, Herdi; Kartadinata, Sunaryo; Taufiq, Agus (Jurnal Kajian Bimbingan dan Konseling, 2019)
Early theoretical and empirical studies have recommended scholars to explore the factors affecting wisdom of counselors. To enact this void, the present study explores the factors affecting wisdom from the perspectives of Indonesian pre-service counselors (henceforth, participants). This study employed survey design to capture the participants’ perceptions. Participants involved in this study were 517 sixth semester pre-service counselors from eleven Guidance and Counseling Departments in Indonesia. Data were collected using questionnaire of Counselor Wisdom Antecedents Scale in the form of Likert five-level scale. The data were then analyzed using descriptive statistics and exploratory factor analysis. The findings captured that there are six factors affecting wisdom of counselor from the perspectives of Indonesian pre-service counselors, namely: (1) social interaction and learning from experiences, (2) values and personality, (3) personal attributes, (4) meta-cognitive skills (critical and depth thinking skills), (5) context-facilitative, and (6) expertise/professionality. The results of this study recommend that counselor educators in the counseling education and supervision programs consider and optimize these factors to develop the wisdom of pre-service counselors.